Signaling in telecommunication networks - Van Bosse, John G. (Wiley series in telecommunications and signal processing, 1998)
This book offers a thorough, accessible examination of signaling in fixed, mobile, and intelligent telecommunications networks. Providing the reader with a solid grasp of the concepts of channel-associated and common-channel signaling, it is an important basic resource for students approaching the subject for the first time as well as engineers and technical managers seeking up-to-date information on the latest technology.